Ethnic And Civilizational Elements In Khalid Fateh Muhammad’s Short Stories - Shehzad, Azmat; Munir, Javed; Akmal, Muhammad (sourcecoder, 2022)
Khalid Fateh Mohammad is a prominent contemporary writer۔He has made a name for himself in novels and fiction. There are various themes in his fiction especially he has played an important role in highlighting Pakistani culture and civilization. He also have an understanding of social problems, hunger, class struggle under the influence of capitalism and sexual and psychological problems of human beings. He also clarified the difference between ancient civilization and modern civilization. Cultural awareness is found in the fictions of Khalid Fateh Mohammad. That is why he has tried to enlighten the generation growing up in the 21st century about the cultural heritage. This article will review the cultural elements of Khalid Fateh Mohammad's fiction.